Answer:
x = ± i, x = ±
![√(2)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/zk4ls2i7rszmygzgqi2kkfexuqtms266jg.png)
Explanation:
Given
- 2
+ 2x² + 4 = 0 ( divide through by - 2 )
- x² - 2 = 0
Use the substitution x² = u , then
u² - u - 2 = 0 ← in standard form
(u - 2)(u + 1) = 0 ← in factored form
Equate each factor to zero and solve for u
u - 2 = 0 ⇒ u = 2
u + 1 = 0 ⇒ u = - 1
Change back into terms of x, that is
x² = 2 ( take the square root of both sides )
x = ±
![√(2)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/zk4ls2i7rszmygzgqi2kkfexuqtms266jg.png)
x² = - 1 ( take the square root of both sides )
x = ±
= ± i
x = ±
← real solutions
x = ± i ← complex solutions